2011
DOI: 10.5539/ijbm.v6n11p190
|View full text |Cite
|
Sign up to set email alerts
|

Brand Preference for Mobile Phone Operator Services in the Cape Coast Metropolis

Abstract: Branding is increasingly being used as a strategy for managing markets in developed countries while developing countries still lag behind. The objective of this study was to assess the level of brand awareness and factors underlying brand preference of mobile phone service brands in Cape Coast market in Ghana. A total of 100 respondents who included individual consumers were selected using accidental simple sampling technique. Primary data was collected using structured interview schedules developed for each c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Availability (Dadzie & Boachie-Mensah, 2011) and gifts (1.9%) also influenced the mobile phone brand choice of the students but these were not significant at the 0.05 level. These indicate that if manufacturers flood the mobile phone market with their brands, they may influence the Ghanaian tertiary students into buying their brands.…”
Section: Discussion Of Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Availability (Dadzie & Boachie-Mensah, 2011) and gifts (1.9%) also influenced the mobile phone brand choice of the students but these were not significant at the 0.05 level. These indicate that if manufacturers flood the mobile phone market with their brands, they may influence the Ghanaian tertiary students into buying their brands.…”
Section: Discussion Of Resultsmentioning
confidence: 86%
“…In all 840 subjects participated in the study. This is justified because some studies (Hao, et al, 2007;Dadzie & Boachie-Mensah, 2011;Boateng & Quansah, 2013;Narteh et al, 2012) have used samples less than this. The respondents were made up of 340 (40.5%) females and 500 (59.5%) males.…”
Section: Methodsmentioning
confidence: 99%
“…The research conducted in Ghania by Dadzie & Mensah (2011), also suggests that most of the people living in Ghania preferred retrieving information from friends and family before purchasing a specific mobile service provider. It is also true in the case of Namibia where the study conducted by Kaapand (2012) concludes that the majority of the population residing in Namibia have similar mobile service provider as their family and friends".…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, one of the variables of this study was selected by comprehending the effects of social factors, including the influence of friends and family in decision making, through the literature. A study in Ghania, West Africa concludes that the influence of friends and family in purchase decision is more than good quality service of mobile service providers (Dadzie & Mensah, 2011). Also, in Singapore, according to Jung & Kau (2004) consumers are highly affected and influenced by their friends and family members while selecting a mobile service provider.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in a study conducted by Rahman et al (2010) on GSM subscribers in Malaysia, the authors stated that price or call fee is the most important factor in operator preference, followed by service quality, service accessibility, and promotional factors, successively. Dadzie and Mensah (2011) identified that the most important factors on the preference for a mobile phone operator are promotion, fee and product availability variables, successively. Gautam and Kumar (2011) analyzed the factors influencing the consumers' preference for a mobile service provider.…”
Section: Introductionmentioning
confidence: 99%